Implementasi Pembelajaran Berbasis Proyek dalam Meningkatkan Kreativitas Belajar Peserta Didik di SMAN 14 Bandung - Ratnawulan, Teti; Wahyu, Agus; Suprayoga, Hari; Sukarna, Haldi Rizkiawan; Yoseptry, Ricky (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research is motivated by the government's efforts to restore post-pandemic learning by implementing an independent curriculum. One of the characteristics of the independent curriculum is implementing project-based learning to support the development of students' character to suit the Pancasila student profile, as is the case at SMAN 14 Bandung which has implemented an independent curriculum by implementing project-based learning. This research aims to obtain an overview of the implementation of project-based learning in increasing students' creativity at SMAN 14 Bandung. This research uses a qualitative approach with descriptive research methods. The general conclusion of this research is to get an overview of project-based learning management in increasing students' creativity at SMAN 14 Bandung. Specific conclusions of this research: project-based learning planning at SMAN 14 Bandung in the form of teaching modules and collaboration project proposals for class X History and Indonesian language subjects, organizing project-based learning at SMAN 14 Bandung involves various elements consisting of the principal, curriculum, teachers, and students, the implementation of project-based learning at SMAN 14 Bandung is running by the project objectives, the results of students' ideas and creativity are in the form of cabaret performances, supervision of project-based learning at SMAN 14 Bandung is carried out by teachers as control of the implementation of project activities, teachers carry out the supervision process starting from preparation, implementation to evaluation of project activities.